Self-concept, anxiety, and performance in mathematics of female at-risk high school learners a phenomenological study - Matias, Celeste Joy O. (College of Education, University of the Philippines Diliman, 2021)
This study aimed to provide an understanding of the lived experiences of female at-risk high school learners in mathematics; their mathematics self-concept, mathematics anxiety, and performance in mathematics. This study used the descriptive phenomenological method to determine the lived experiences of eight female at-risk high school students. This methods allowed the participants to provide rich descriptions of the "whatness" of a female at-risk high school learner in mathematics, without being influenced by current theories on that matter, that cannot be deduced from quantitative responses. The themes that emerged from their narratives describes how the at-risk learners' self-concept in mathematics mirrored how they looked into their own selves versus others in their environment. A look into their past revealed how their aversion to mathematics was borne, and what steered them to a pathway of positivity. Furthermore, comprehension in mathematics was shown to be the gatekeeper for positive emotional experiences. Without the key to that gate, at-risk learners battled with stress and anxiety that festered both their mind and their bodies. To shield themselves from being subjected to pain, they leaned on maladaptive strategies. To address the root of their pain, they bridged the gaps in their mathematical skills by developing adaptive coping strategies. From these themes, a framework was constructed to highlight the relationships between the mathematics self-concept, mathematics anxiety, and performance of female at-risk high school learners in mathematics.